PENGARUH GAYA HIDUP DAN LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN TENAGA KERJA MUDA DI JAKARTA - Nurul Amalia Putri; Diyan Lestari (LPMP Imperium, 2019)
The main purpose of this research is to analyze the impact of lifestyle and financial literacy on financial management. The method of this research is quantitative research. The population of this research are young workers in Jakarta with accidental sampling tehniques using 30 samples as a pre test and 135 samples as a main test. The analysis techniques use multiple regression, t test and F test. The result of t test showed that lifestyle and financial literacy partially affected on financial management. And the result of F test showed that lifestyle and financial literacy simultaneous affected on financial management.